Comparison of surgical outcomes between patients undergoing trans-oral endoscopic thyroid surgery combined with trans-thoracoareolar approach and conventional open surgery - Shi, Youyuan; Zhang, Lu; Liu, Chang; Wang, Yong; Zhang, Hailin; Lin, Xiuan (Frontiers in Surgery, 2022)
Over the past decades, remote-access thyroid surgery has been widely developed in the treatment of thyroid carcinoma, which can help patients to avoid cosmetically displeasing scarring. In this research, we collected and review our experience with endoscopic thyroidectomy with neck dissection via trans-thoracoareolar approach combined with trans-oral approach over a 3-year period. They were all diagnosed with thyroid carcinoma, and two of them had a complication of Hashimoto's thyroiditis. No patients were dissatisfied with the postoperative cosmetic results. One patient had numbness in the lower lip, but the symptom disappeared 1 month later. No infection, hemorrhage, or air embolism occurred. Pain and numbness in the endoscopic thyroid surgery group were slighter than in those who had open surgery. The present study aims to compare the feasibility and safety of trans-thoracoareolar approach combined with trans-oral approach to conventional open surgery.